IL-4 down-regulates the responsiveness of human intraepithelial lymphocytes - EBERT, E C (Blackwell Science Inc, 1996)
IL-4 is an important regulator of intestinal inflammation, yet little is known regarding its action on intestinal lymphocytes. Intestinal lymphocytes were isolated from jejunal mucosa of patients undergoing gastric bypass operations for morbid obesity. The impact of IL-4 was measured by its effects on proliferation using (3)H-thymidine incorporation, IL-2 production using the CTLL assay, and IL-2 receptor generation using immunofluorescence. The production of IL-4 was measured by ELISA. IL-4 significantly inhibited the proliferation of intraepithelial lymphocytes (IEL) to a variety of stimuli as well as the development of lymphokine-activated killer (LAK) cells. In contrast, it had no effect on the proliferation of CD8(+) T cells from peripheral blood. The inhibitory effect of IL-4 on IEL did not occur during activation, since IL-2 production and receptor expression were not altered. Rather, it occurred during cell cycling, since over 50% inhibition resulted whether IL-4 was added at the initiation of an IL-2-stimulated culture or after 24 or 48 h incubation. IL-4 was secreted by activated lamina propria lymphocytes (LPL) but not by IEL. IL-4,produced by activated LPL, may enter the epithelial compartment and down-regulate responsiveness of IEL.